2009
DOI: 10.1107/s1744309109047381
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and preliminary crystallographic characterization of glutamine synthetase fromMedicago truncatula

Abstract: The condensation of ammonium and glutamate into glutamine catalyzed by glutamine synthetase (GS) is a fundamental step in nitrogen metabolism in all kingdoms of life. In plants, this is preceded by the reduction of inorganic nitrogen to an ammonium ion and therefore effectively articulates nitrogen fixation and metabolism. Although the three-dimensional structure of the dodecameric bacterial GS was determined quite some time ago, the quaternary architecture of the plant enzyme has long been assumed to be octam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 23 publications
1
29
0
Order By: Relevance
“…Recently it has been reported that plant GS holoenzyme has a decameric structure composed of two face-to face pentameric rings of subunits, with active sites formed between every two neighboring subunits within each ring [4,5]. Phylogenetic studies of nucleotide and amino acid sequences have shown that genes for chloroplastic and cytosolic GS in plants form two sister groups with a common ancestor which diverged by duplication before the split between angiosperms and gymnosperms [6].…”
Section: Introductionmentioning
confidence: 99%
“…Recently it has been reported that plant GS holoenzyme has a decameric structure composed of two face-to face pentameric rings of subunits, with active sites formed between every two neighboring subunits within each ring [4,5]. Phylogenetic studies of nucleotide and amino acid sequences have shown that genes for chloroplastic and cytosolic GS in plants form two sister groups with a common ancestor which diverged by duplication before the split between angiosperms and gymnosperms [6].…”
Section: Introductionmentioning
confidence: 99%
“…Previously characterized factors determining the selectivity of Tyr nitration in proteins include the exposure of the aromatic ring at the surface of the protein and the location of the Tyr residue on a loop and in the neighborhood of a negatively charged residue (Souza et al, 1999;Ischiropoulos 2003;Chaki et al, 2009). For the identification of the Tyr residue(s) potentially nitrated in MtGS1a, we analyzed the structural environment within the three-dimensional structure of the protein and identified Tyr-167 to be favorably placed for nitration (Seabra et al, 2009). The residue is located in a solvent-accessible loop, close to the enzyme active site and in close proximity to a basic residue (Lys-137).…”
Section: Discussionmentioning
confidence: 99%
“…6). From the analysis of the three-dimensional structure of MtGS1a (Seabra et al, 2009), it is predicted that only the residues Tyr-167 and Tyr-263 are placed within a local environment favorable to nitration (Abello et al, 2009); additionally, their modification is likely to affect GS activity. To investigate whether any of these residues could be a regulatory nitration site and account for the specific susceptibility of MtGS1a to inactivation by nitration, we mutated residues Tyr-167 and Tyr-263 to Phe by site-directed mutagenesis and tested the susceptibility of the mutated proteins to inactivation induced by TNM.…”
Section: Identification Of Tyr-167 As a Relevant Nitration Sitementioning
confidence: 99%
“…Indeed, based on x-ray crystallography data from maize (Unno et al, 2006) and Medicago truncatula (Seabra et al, 2009), it has been suggested that plant GSs are decameric enzymes consisting of two face-to-face oriented pentameric rings. Therefore, the pentameric GS identified in this study corresponds to a single pentameric ring.…”
Section: Homo-multimeric Protein Complexesmentioning
confidence: 99%